MEMBUAT PROSES MANAJEMEN BERKUALITAS - Efni Ramli (AL-ISHLAH: Jurnal Pendidikan, 2017)
The quality of the organization can be measured by customer satisfaction through continuous process improvement management. The strategy used in leading to quality management is Strategy Total Quality Management (TQM). Process to TQM involves many elements such as professional leaders, empowerment and teamwork, quality products and consistent service for customers and organizational management appraisals.